Serum 25‐hydroxyvitamin D, folate and cobalamin and their association with brain volumes and white matter integrity in a sample of urban adults: Epidemiology / Innovative methods in epidemiology (i.e., assessment methods, design, recruitment strategies, statistical methods, etc.). (7th December 2020) - Beydoun, May A; Shaked, Danielle; Hossain, Sharmin A; Beydoun, Hind A; Katzel, Leslie; Davatzikos, Christos; Gullapalli, Rao; Seliger, Stephen; Erus, Guray; Evans, Michele K; Zonderman, Alan; Waldstein, Shari
Abstract: Background: Lower vitamin D, folate and cobalamin status were linked to cognitive deficits, pending mechanistic elucidation. We explored whether serum 25‐hydroxyvitamin D [25(OH)D], folate and cobalamin are related to brain volumes and white matter (WM) integrity. Method: Between 183 and 240 community‐dwelling participants [Baltimore city, Agev1 : 30‐64y] had vitamin concentrations [at visit 1(v1 )] and Magnetic Resonance Imaging (MRI) measures at follow‐up (vscan ), after a mean±SD=5.70y±1.90. Multivariable‐adjusted linear regression analyses were conducted using structural and diffusion magnetic resonance imaging (sMRI/dMRI) with increasing segmentation specificity as outcomes and each vitamin as an exposure (v1 and annual rate of change (v2 ‐v1 ) over an average of 4.65y), stratifying by agev1 (>50y/≤50y), sex, race (Whites/African Americans) and poverty status group. Top 10 ranked adjusted associations were statistically significant if passing familywise Bonferroni (FWER) criteria at an α=0.05, while false discovery rates (FDR, q‐value)<0.10 and standardized effect size (b) criteria were used for trend findings. Result: We found mostly significant (FWER<0.05) direct associations of 25(OH)D(v1 ) with WM volumes (overall/males), with occipital and parietal WM [overall, males and Agev1 >50y], and with the left occipital pole volume. Folate(v1 ), 25(OH)D(v1 ) and 25(OH)D(v2 ‐v1 ) trended towards better WM integrity in several regions, mainly the anterior limb of the internal capsule (ALIC) and the hippocampus [q<0.10 per vitamin, b≥0.20 for 25(OH)D(v1 ) and Folate(v1 ); FWER<0.05 for 25(OH)D(v2 ‐v1 )], while folate trended towards lower right temporal pole volume (Whites/>50y) and longitudinal increase (v2 ‐v1 ) in cobalamin trended towards larger volumes within the inferior frontal gyrus. Conclusion: Serum 25(OH)D was consistently linked to greater occipital and parietal WM volumes. WM integrity in ALIC was associated with higher 25(OH)D and folate status, while folate was inversely related to temporal GM volumes. Cobalamin increase over time trended towards larger inferior frontal gyrus volumes. Future interventions should test vitamin supplementation against regional volumetric and diffusion brain markers.